2015
DOI: 10.1159/000371628
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus and Macrosomia: A Literature Review

Abstract: Background: Fetal macrosomia, defined as a birth weight ≥4,000 g, may affect 12% of newborns of normal women and 15-45% of newborns of women with gestational diabetes mellitus (GDM). The increased risk of macrosomia in GDM is mainly due to the increased insulin resistance of the mother. In GDM, a higher amount of blood glucose passes through the placenta into the fetal circulation. As a result, extra glucose in the fetus is stored as body fat causing macrosomia, which is also called ‘large for gestational age'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
442
3
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(548 citation statements)
references
References 42 publications
17
442
3
23
Order By: Relevance
“…In addition; Kc et al, reported that the fetal macrosomia is a common adverse outcome of GDM if unrecognized and untreated properly [29]. Kc et al, concluded that the fetal macrosomia increases the risk of shoulder dystocia, clavicle fractures, brachial plexus injury, NICU admissions, cesarean delivery, postpartum hemorrhage, and vaginal lacerations [29].…”
Section: Negative Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…In addition; Kc et al, reported that the fetal macrosomia is a common adverse outcome of GDM if unrecognized and untreated properly [29]. Kc et al, concluded that the fetal macrosomia increases the risk of shoulder dystocia, clavicle fractures, brachial plexus injury, NICU admissions, cesarean delivery, postpartum hemorrhage, and vaginal lacerations [29].…”
Section: Negative Outcomementioning
confidence: 99%
“…Kc et al, concluded that the fetal macrosomia increases the risk of shoulder dystocia, clavicle fractures, brachial plexus injury, NICU admissions, cesarean delivery, postpartum hemorrhage, and vaginal lacerations [29].…”
Section: Negative Outcomementioning
confidence: 99%
“…Finally, birth weight is also considered as a significant predictor of childhood obesity risk [26]. In GDM pregnancy, maternal hyperglycemia leads to fetal hyperinsulinemia, which increases fetal growth and then the risk of being born with a high birth weight [27]. Some authors suggested that the association between exposure to GDM and obesity risk in childhood would be partially explained by elevated birth weight, highlighting the importance to consider this cofactor in analyses [28].…”
Section: Breastfeedingmentioning
confidence: 99%
“…3 The incidence of mortality in preterm newborns is higher if IUGR is also present, increasing the perinatal mortality percentages by two to ten times. 9 Just as IUGR may result in adults with diseases, macrosomia in adulthood can also trigger obesity, dyslipidemia, hypertension and type 2 diabetes. 8 Fetal macrosomia is the term used to define fetuses or newborns considered abnormally large, weighing 4000 grams or more; large for gestational age (LGA) newborns are those who are above the 90 th percentile for gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Macrosomia is observed among cases with poorly controlled diabetes, those with long evolution and those with vascular alterations. 8 Understanding the relevance of IUGDs as a predisposing factor to the increased risk of fetal/ neonatal morbidity and mortality, and recognizing deviations as well as their etiopathogenesis is extremely important, 9 being a fundamental task in quality prenatal care.…”
mentioning
confidence: 99%